Endothermy makes fishes faster but does not expand their thermal niche - Donohue, Ian; Payne, Nicholas (My University, 2021)
Regional endothermy has evolved several times in marine fishes, and two competing hypotheses are generally proposed to explain the evolutionary drivers behind this trait: thermal niche expansion and elevated cruising speeds. Evidence to support either hypothesis is equivocal, and the ecological advantages conferred by endothermy in fishes remain debated. By compiling published biologging data and collecting precise speed measurements from free-swimming fishes in the wild, we directly test whether endothermic fishes encounter broader temperature ranges, swim faster or both. Our analyses avoid several complications associated with earlier tests of these hypotheses, as we use precise measurements of the thermal experience and speed of individual fish. Phylogenetically-informed analyses of 89 studies reporting temperature ranges encountered by tagged fishes reveal that endotherms do not encounter broader temperature ranges than their ectothermic counterparts. In contrast, speed measurements from 45 individuals (16 species, of which four were regional endotherms) show that endothermic fishes cruise ~1.6 times faster than ectotherms, after accounting for the influence of body temperature and body mass on speed. Our study shows that regionally endothermic fishes—those with the ability to conserve metabolically derived heat through vascular countercurrent heat exchangers and elevate the temperature of internal tissues—swim at elevated cruising speeds, although not as fast as previously thought. Contrary to previous studies of endothermy's role in thermal niche expansion, our results suggest the significance of endothermy in fishes lies in the advantages it confers to swimming performance rather than facilitating the occupation of broader thermal niches. Given speed's major influence on metabolic rate, our updated speed estimates imply endotherms have lower routine energy requirements than current estimates. Our findings shed light on the evolutionary drivers of regional endothermy in fishes and question the view that the trait confers resilience to climate change through broader thermal tolerance than that of ectotherms.
PUBLISHED
Keywords: biologging; comparative analysis; elevated cruising speeds; energetics; fish body temperature; regional endothermy; swimming speed; thermal niche expansion; Smart & Sustainable Planet